UPAYA MENINGKATKAN KEMAMPUAN PASSING BAWAH BOLA VOLI PADA MATA PELAJARAN PJOK MELALUI MODIFIKASI ALAT SISWA KELAS IV SDN 027 PARIT BARU KECAMATAN TAMBANG KABUPATEN KAMPAR - Darmilis Darmilis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low ability of low-tide volleyball students in grade IV SDN 027 Parit BaruKecamatan Tambang. This study aims to improve the ability of pasing under PJOK subject volleyball throughmodification of tools. The subjects of this study were all fourth grade students of SDN 027 Parit Baru,Kecamatan Tambang, totaling 20 people. The form of research is classroom action research. This researchinstrument consists of performance instruments and data collection instruments in the form of observation sheetsof teacher activities and student activities. Based on the results of the study, it can be seen that the students'completeness before the action reached 40%, while the first cycle achieved completeness by 70% and in thesecond cycle the students' mastery increased to 85%, so that with this result the students' completeness hadreached 80% of the success in class actions. Based on the results of the study it can be concluded that throughmodification of the tool can improve the ability to pass under the fourth grade students of SDN 027 Parit Baru,Kecamatan Tambang.